Pengaruh Aksesibilitas Laporan Keuangan, Transparansi, Partisipasi Masyarakat, Dan Kompetensi Aparatur Desa Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Empiris Pada Pemerintah Desa Di Kabupaten Kampar) - Reka Hendra Yani; Yusralaini Yusralaini; Aulia Pinto Atami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This research aims to examine the effect of Financial Report Accessibility,Transparency, Community Participation, and Village Apparatus Competence on theAccountability of Village Fund Management in Kampar Regency. The researchsample consisted of 125 respondents from 25 villages selected using a purposivesampling method. This study employed a quantitative approach with data analysisconducted using the SPSS application, including descriptive and inferentialstatistical analyses, as well as hypothesis testing. The results show that all fourvariables—Financial Report Accessibility, Transparency, CommunityParticipation, and Village Apparatus Competence—have a positive and significanteffect on the Accountability of Village Fund Management. These findings provideimportant implications for policymakers and village stakeholders to strengthenthese factors in order to improve accountability in village fund management. Keywords: Financial Report Accessibility, Transparency, CommunityParticipation, Village Apparatus Competence, Accountability ofVillage Fund Management